Benita Riaubienė. Resultative secondary predication in European languages - Mikulskas, Rolandas (Lietuvių kalba, 2015)
Doctoral dissertation (Humanities, Philology (04 H)), Vilnius: Vilnius University, 2015, p. 184.
Keywords: none